2004
DOI: 10.1002/cncr.20637
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of disease progression in patients who fail to achieve an undetectable prostate‐specific antigen level after undergoing radical prostatectomy

Abstract: BACKGROUNDTo the authors' knowledge, the natural history of disease progression to distant metastasis is unknown in men who fail to achieve an undetectable prostate‐specific antigen (PSA) level after radical retropubic prostatectomy (RRP),. The authors assessed the clinical outcome of men with a persistently detectable PSA level after RRP for clinically localized prostate carcinoma.METHODSBetween 1989 and 2002, 160 men failed to achieve an undetectable PSA level (≥ 0.1 ng/mL) after undergoing RRP for clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 26 publications
2
53
0
2
Order By: Relevance
“…Even without risk factor of biochemical recurrence, the progression rate was significant. Rogers et al [6] demonstrated that 38% of men who fail to achieve an undetectable PSA level will experience slow disease progression and remain free of distant metastases for C7 years. Nevertheless, 32% of patients in this study were reported to develop metastases within 3 years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even without risk factor of biochemical recurrence, the progression rate was significant. Rogers et al [6] demonstrated that 38% of men who fail to achieve an undetectable PSA level will experience slow disease progression and remain free of distant metastases for C7 years. Nevertheless, 32% of patients in this study were reported to develop metastases within 3 years.…”
Section: Discussionmentioning
confidence: 98%
“…However, men with persistently elevated PSA immediately after surgery, even less than 0.2 ng/ml, seem to be at higher risk for biochemical recurrence, disease progression, and disease-specific mortality [6]. Several studies have used PSA persistence as a marker of adverse outcome, but its significance remains unclear.…”
Section: Introductionmentioning
confidence: 96%
“…Early manifestation of the oral soft tissues metastases resemble reactive lesions, such as pyogenic granuloma and peripheral giant cell granuloma. Because of its rarity, the diagnosis of a metastatic lesion in the oral region is challenging, both to the clinician and to the pathologist, in recognizing that a lesion is metastatic and in determining the primary site [10]. Torn Daley in 2011, reported 38 cases of oral metastases, mostly to the mandible followed by the gingiva, mucosa and the alveolar ridge, the most common primary sites were the prostate 8 cases, the lung 7 cases, the breast 5 cases, squamous cell carcinomas 4 cases, renal cancer 3 cases, ca colon 2 cases, hepatocellular cancer 2 cases, thyroid cancer one case and unknown primary 6 cases [11].…”
Section: Discussionmentioning
confidence: 99%
“…A PSADT < 10-month failure was assigned to men with a persistently positive PSA level at 1 month after RP without evidence of residual prostatic tissue in the surgical bed on magnetic resonance imaging (MRI), because this has been associated with a high risk of distant metastatic disease. 21 Given that a PSADT of 10-month failure is also possible, we modeled the interval to PSADT < 10-month failure using a competing risks method. Specifically, univariable and multivariable Fine and Gray's competing risk regression analysis was used to assess whether an increasing GPC was associated with an increased risk of PSADT < 10-month failure, adjusting for age, PPB, and risk group.…”
Section: Discussionmentioning
confidence: 99%